2010
DOI: 10.1002/lary.20889
|View full text |Cite
|
Sign up to set email alerts
|

The early postoperative course of surgical sleep apnea patients

Abstract: The incidence of respiratory events requiring intervention in the early postoperative course of OSA patients was low (3.4%). Routine postoperative inpatient monitoring may not be required in many cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…This is in line with recent work from our center wherein we examined 121 patients with sleep study‐proven OSA (AHI 31.9 ± 22.7) who underwent multilevel sleep apnea surgery. The incidence of nursing intervention in response to respiratory complications was 3.4%, which was significantly less than quoted by the ASA guidelines . An even more recent review by Pang's group in Singapore demonstrated a low 1.8% incidence of respiratory complications in 487 patients, with eight of the nine complications being noted within 3 hours of surgery while still in PACU, and six of nine being simple desaturations with no adverse consequences .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is in line with recent work from our center wherein we examined 121 patients with sleep study‐proven OSA (AHI 31.9 ± 22.7) who underwent multilevel sleep apnea surgery. The incidence of nursing intervention in response to respiratory complications was 3.4%, which was significantly less than quoted by the ASA guidelines . An even more recent review by Pang's group in Singapore demonstrated a low 1.8% incidence of respiratory complications in 487 patients, with eight of the nine complications being noted within 3 hours of surgery while still in PACU, and six of nine being simple desaturations with no adverse consequences .…”
Section: Discussionmentioning
confidence: 79%
“…All patients who screened for admission by SORT criteria were transferred to our institution's sleep apnea overnight‐monitoring room for 24 hours of continuous observation. Complications, if any, were recorded as per the protocol of our previous study (see Table ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the incidence of respiratory events (all being oxygen desaturations) in the early postoperative course was low (3.4%), and that all such patients were all identified within 4 hours of surgery. The incidence of adverse respiratory events was too small in this study to be able to predict risk factors thereof 6…”
Section: Literature Reviewmentioning
confidence: 80%
“…More recently, studies have argued that in selected patients UPPP can be performed as an outpatient surgery [6-10]. These studies have consistently shown that complications rates are low, that more severe complications tend to occur while still in recovery room, and no postoperative mortality.…”
Section: Introductionmentioning
confidence: 99%